Ultrasonically Produced Porous Sponge Layer on Titanium to Guide Cell Behavior. Issue 4 (15th January 2016) - Kopf, Jessica; Ulasevich, Svetlana; Baidukova, Olga; Zhukova, Yulia; Dunlop, John W. C.; Fratzl, Peter; Rikeit, Paul; Knaus, Petra; Poznyak, Sergey K.; Andreeva, Daria V.; Skorb, Ekaterina V.
Abstract : We present the prospects of ultrasonically formed mesoporous sponge layer (TMS), to guide cell behavior in comparison to flat titania and an anodized titania surface (TNT). The taking into account parameters to compare are: (i) surface roughness, (ii) pore size, and (iii) in regularity of the nanopore arrangement.